Immersive Learning on Environmental Chemistry Concepts through e-SULAM - Rafeah, Wahi; Showkat, Ahmad Bhawani (UNIMAS Publisher, 2023)
Environmental Chemistry 2 (STK2063) is offered in semester 2 for Year 2 students in BSc (Hons) Resource Chemistry. In this course environmental issues relating to solid waste, wastewater and hazardous waste are viewed in the context of their treatments. This course has been implementing service learning (SULAM) as a part of immersive learning approach since Semester 2, 2017/2018. In previous years, i.e. 2017/2018, and 2018/2019, the course assessment includes either final examination (40%, session 2017/2018), or mid-term examination (30%, session 2018/2019). Although SULAM implementation has generally improved the CLO achievement throughout the years, the pen and paper examination was found to be one of the reason to why some of the students were not able to achieve the intended CLOs. Instructors were not sure on the effectiveness of such examination in creating a deep learning experience for students. Therefore, in semester 2, 2019/2020, the mid-term examination was replaced with case-study analysis to (1) encourage higher order thinking skills among students, and (2) cultivate the sense of commitment and responsibility among students to find innovative solutions to waste management issues. In addition, students’ e- SULAM projects including group discussion and engagement with target community were implemented on online platforms. Students’ reflection on their e-SULAM projects was recorded on their e-portfolio. Implementation of immersive learning through blended learning in this course has resulted in improved CLO achievement as compared to the past two years. Students’ reflection on their learning experience in this course implied the effectiveness of immersive learning (blended learning) approach in this course.